Unsociability and social adjustment in Chinese preschool migrant children: the moderating role of receptive vocabulary - Zhu, Jingjing; Xiang, Shuhui; Yin, Xiaoqi; Li, Yan (Frontiers in Psychology, 2024)
The objective of the present investigation was to examine the associations between unsociability, receptive vocabulary, and indicators of social adjustment in a cohort of young migrant children residing in urban regions of mainland China. The study mainly aimed to investigate the potential moderating influence of receptive language on these associations. The study involved 148 young children (82 boys, 66 girls, Mage = 62.32 months, SD = 6.76) enrolled in preschools or kindergartens in Shanghai, People's Republic of China. Multiple sources of assessment were utilized, encompassing evaluations from mothers (about child unsociability), teacher (assessing social adjustment), and standardized tests (measuring receptive vocabulary). The results indicated that the relations between unsociability and peer exclusion were more positive among children with lower levels of receptive vocabulary but not significant for children with higher levels of receptive vocabulary. Similarly, the relations between unsociability and peer exclusion were more negative among children with lower levels of receptive vocabulary but not significant for children with higher levels of receptive vocabulary. Thus, this study informs us about how receptive vocabulary is jointly associated with unsociable children's development. As well, the findings highlight the importance of considering the meaning and implication of unsociability in Chinese culture.mitigating the likelihood of adverse outcomes. Therefore, this study investigates the potential protective role of receptive vocabulary to unsociability and social adjustment among Chinese migrant children. In addition, previous researches on unsociability and social adjustment were mainly focused on school-age children, with relatively little research on preschoolers, particularly Chinese migrant preschoolers. On the other hand, considering the role of culture in exploring unsociability and the importance of promoting equity in education, it is necessary to take into account the role of culture and the use of migrant children as research participants. Therefore, the primary objective of this research is to investigate the potential moderating influence of receptive vocabulary on the association between unsociability and social adjustment among Chinese preschool migrant children.